2010
DOI: 10.1111/j.1600-0536.2009.01696.x
|View full text |Cite
|
Sign up to set email alerts
|

Hairdressers with dermatitis should always be patch tested regardless of atopy status

Abstract: We present findings from the largest cohort of hairdressers patch tested from a single centre. It is necessary to patch test hairdressers with dermatitis, regardless of a history of atopy. Strategies to reduce prevalence of allergic contact dermatitis are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
39
2
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 28 publications
7
39
2
4
Order By: Relevance
“…Therefore, we cannot assume that similar durations of exposure meant equal doses of exposure. Hairdressers carry out a variety of tasks and may not be continuously exposed to the same agents, especially with regard to potential allergens 5,9) . The ONAP study stated that hairdressing brings with it a higher risk of occupational asthma 4) , and in the present study, we found a definite impact of the hairdressers'jobs on their respiratory health, with significantly higher workplace exposure-induced respiratory symptoms in the self-employed group than in the wage-earning group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, we cannot assume that similar durations of exposure meant equal doses of exposure. Hairdressers carry out a variety of tasks and may not be continuously exposed to the same agents, especially with regard to potential allergens 5,9) . The ONAP study stated that hairdressing brings with it a higher risk of occupational asthma 4) , and in the present study, we found a definite impact of the hairdressers'jobs on their respiratory health, with significantly higher workplace exposure-induced respiratory symptoms in the self-employed group than in the wage-earning group.…”
Section: Discussionmentioning
confidence: 99%
“…Occupational hand contact dermatitis was defined as clinical eczema or irritative cutaneous diseases with work-related occurrence. In hairdressing, wet work from washing and handling damp hair results in exposure to surfactants that may lead to skin irritation 5) . Regarding musculoskeletal injuries, we focused (not only) on disorders in the upper body related to repetitive movements.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Persuphates, ethanol and ammonia present in hair bleaches were associated with asthma and contact dermatitis in hairdressers [14,15,29]. In 2005, the UK's Health and Safety Executive reported that, the highest incidence of occupational skin diseases (98 per 100,000) was among hairdressers [31]. Also, hand eczema was higher among the Swedish hairdressers compared to the general population [26].…”
Section: Introductionmentioning
confidence: 97%
“…Krecisz et al revealed that nickel was the most frequently sensitizing skin allergen in the hairdresser apprentices group. It is thought to be rather non-occupational sensitization, resulting from skin exposure to metal objects, such as jewellery, clothing accessories and particularly from piercing [17], however the release of nickel ions from nickel-containing tools exposed to thioglycolic acid in permanent wave solutions may also contribute to the high prevalence of sensitization in this professional group [18].…”
Section: Discussionmentioning
confidence: 99%